Simulation for Modified Bitumen Incorporated with Crumb Rubber Waste for Flexible Pavement - Mohan, A.; Dinesh Kumar, R.; J., Satchidanandam (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This research paper specifies on modified bitumen using recycled plastic waste and crumb rubber for sustainable usage of flexible pavement construction. In current scenario flexible payments fail mostly due to cracking and fatigue in localized areas which decrease the duration of life of the pavement thereby reducing the indented purpose. So this paper focuses on providing an alternative to the already present normal bitumen in flexible pavements thereby reducing landfill problems, increase in efficiency, reducing the usage of raw materials thereby providing a better alternative. The major cause of failure in flexible pavements is defined by localized depression or settling locally. To overcome this problem this research paper focuses on adding additives such as recycled plastic and crumb rubber for reducing the localized failure occurrence. These additives are added at the rate of 2%, 4%, 6%, 8%, 10% for both recycled plastic and crumb rubber to find the mix ratio at which shear strength and ductility is highest for the modified bitumen. Ductility test and shear resistance test are performed in the laboratory to verify the results and provide the necessary information. It is concluded from this study that addition of HDPE and crumb rubber showed a significant increase in durability properties of the binder.